Progression of fibrosis in chronic hepatitis C - Ghany, Marc G; Kleiner, David E; Alter, Harvey; Doo, Edward; Khokar, Farooq; Promrat, Kittichai; Herion, David; Park, Yoon; Liang, T Jake; Hoofnagle, Jay H (Gastroenterology (New York, N.Y. 1943), 2003)
Fibrosis is the hallmark of hepatic cirrhosis, worsening of which is probably the best surrogate marker for progression of chronic liver disease. We evaluated a large cohort of patients with chronic hepatitis C (CHC) using liver histology to assess the rate and predictors of progression of fibrosis. The cohort consisted of 123 patients with CHC who underwent 2 liver biopsies 4-212 months (mean, 44 months) apart without intervening treatment. Liver histology was graded using the histology activity index (score, 0-18) and fibrosis staged using a scoring system of 0 (no fibrosis) to 6 (cirrhosis). Among 123 patients, 48 (39%) showed progression in fibrosis scores, 46 (37%) showed no change, and 29 (24%) showed improvement. Of those with worsening fibrosis, 75% had a 1-point increase and 25% a 2-point or greater increase in scores, and 9% showed progression to cirrhosis. The overall rate of progression was 0.12 fibrosis units per year, a rate that predicts progression to cirrhosis in 50 years if progression was linear. The rate of fibrosis progression was variable, and it was higher among older patients, those with higher serum alanine and aspartate aminotransferase levels, and those with the most extensive periportal necrosis on initial liver biopsy. The best predictors of fibrosis progression in CHC are the extent of serum aminotransferase elevations and the degree of hepatocellular necrosis and inflammation on liver biopsy. These findings support the recommendation that patients with normal aminotransferase levels and mild liver histology can safely defer treatment.